Chronic aftershock: how 9/11 shaped present-day France - Mathy, Jean-Philippe (McGill-Queen’s University Press, 2021)
"The terrorist attacks of 11 September 2001 were a local event that nevertheless elicited strong reactions throughout the world. The unprecedented strike on the continental United States, its instantaneous broadcast, and its global stakes placed 9/11 at the centre of ideological debates that still rage today. The impact was especially felt in France. Chronic Aftershock looks at the significance of 9/11 in France as documented by prominent politicians, public intellectuals, journalists, sociologists, political scientists, philosophers, novelists, and conspiracy theorists. In his comprehensive account, Jean-Philippe Mathy addresses the rise of a small but influential group of self-described "anti-anti-Americans" who shared the views of American neoconservatives in support of regime change in Iraq; the media controversy involving French Evangelical churches’ response to the religious views of George W. Bush; the widespread "I am Charlie" movement following the attacks against the offices of Charlie Hebdo; and the unending French national debate on the place of the Muslim community in a secular, universalist republic. The book also considers the November 2015 Islamist attacks in Paris, often described as "the French September 11". Combining approaches from intellectual history, cultural studies, and literary criticism, Chronic Aftershock explores the legacy of 9/11 and recent instances of transatlantic divide to provide an innovative and timely assessment of the radicalized violence that remains a major threat in today’s world."--